What Does the Situation Say? Theorizing Multiple Understandings of Climate Change. (3rd September 2021) - Schnegg, Michael
Abstract: Our ways of knowing the weather are transforming. Climate change modifies weather patterns, and the globalization of scientific knowledge promotes new ways of making the weather intelligible. Following both transformations, I explore how Damara pastoralists (ǂNūkhoen) in Namibia entertain various Indigenous, religious, political, and scientific explanations for the most distressing weather‐related phenomenon they experience—the lack of rain. Integrating qualitative and quantitative data, my ethnography reveals how people combine knowledge from multiple, even contradictory, registers to explain one situation, and use a different combination of sources to explain another. To understand this, I develop a phenomenological framework that shows how being‐in‐the‐world creates a phenomenon situationally. If phenomena differ depending on how we enact the world, it is unsurprising that these phenomena would then entail different explanations. With this, I theorize why people make sense of climate change in multiple ways, and why they move between them.